Pelatihan Self-Efficacy untuk Meningkatkan Adaptive Performance pada Guru Anak Berkebutuhan Khusus di SLB X - Josefanny; A.J. Tjahjoanggoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Adaptive performance behavior in the workforce has a big role for agencies and companies. Especially for workers who in many situational changes, namely teachers of children with special needs. The aim of this research is to find out whether self-efficacy training can improve adaptive performance behavior in teachers of children with special needs at SLB X. The research uses a quantitative approach with the type of experimental research. This research design uses a One Group Pre-Test Post-Test design. The data distribution technique used purposive sampling, namely to 20 teachers of children with special needs at SLB X. The data collection method used a questionnaire with likert scale. The research instrument used the Career Self Efficacy Sources Scale (CSESS) by Bandura (1977) and the Individual Adaptability Measure (I-ADAPT-M) by Marlow and Calarco (2016). The results show that self-efficacy training has an influence on increasing adaptive performance behavior in teachers of children with special needs at SLB X so the researcher’s hypothesis is accepted.